2005
DOI: 10.1016/j.leukres.2004.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Normal neutrophil maturation is associated with selective loss of MAP kinase activation by G-CSF

Abstract: Although both GM-CSF and G-CSF activate p42/44 MAPK in neutrophil progenitors, the ability of G-CSF to cause MAPK activation is lost in mature neutrophils, while GM-CSF exposure still causes activation. The mechanism of this differential effect related to maturation status has not been explored. We verified that G-CSF and GM-CSF receptors remain functional on purified mature neutrophils by demonstrating that both cytokines caused phosphorylation of STAT3. However, only GM-CSF was capable of activating MAPK as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, Dong et al [71] report a weak interaction between the C-terminal tail of the G-CSFR and Shp1 when overexpressed in 293T cells, which is required to limit the activation of Stat3 but not Akt or MAPK. Baumann et al [72] suggest that G-CSF signaling activates MAPK during neutrophil maturation to promote proliferation, but upregulation of Shp1 inhibits this pathway to enhance differentiation in mature neutrophils. More recently, CEACAM-1, which is an ITIM-containing receptor expressed highly on the surface of neutrophils and up-regulated upon neutrophil activation [73], has been suggested to mediate Shp1 inhibition of G-CSF signaling.…”
Section: Neutrophilsmentioning
confidence: 99%
“…However, Dong et al [71] report a weak interaction between the C-terminal tail of the G-CSFR and Shp1 when overexpressed in 293T cells, which is required to limit the activation of Stat3 but not Akt or MAPK. Baumann et al [72] suggest that G-CSF signaling activates MAPK during neutrophil maturation to promote proliferation, but upregulation of Shp1 inhibits this pathway to enhance differentiation in mature neutrophils. More recently, CEACAM-1, which is an ITIM-containing receptor expressed highly on the surface of neutrophils and up-regulated upon neutrophil activation [73], has been suggested to mediate Shp1 inhibition of G-CSF signaling.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Furthermore, SHP-1 has also been implicated in the regulation of the MAPK pathway in human neutrophils, brain pericytes, and the renal cortex of diabetic mice (41,42). Therefore, to examine the involvement of MAPKs pathway in LPS-induced IL-6 production, we compared the activation of MAPK family members in LPS-stimulated BMDMs derived from me/me and normal mice.…”
Section: Productionmentioning
confidence: 99%
“…It is of note that the association was found to be strong in resting cells and was reduced during interferon-␣ (IFN-␣) stimulation of a T cell line [5]. Given the wide range of its ligand, it is likely that SHP-1 plays various roles in cells besides inhibition of cell activation, including maturation of receptors [6] and of cells such as polymorphonuclear leukocytes (PMN) or platelets [7][8][9][10][11], and that specific adaptor proteins mediate each of these roles. Moreover, it was shown that SHP-1 might be the phosphatase responsible for down-regulation of mitogenactivated protein kinase (MAPK) activation by granulocytecolony stimulating factor (G-CSF) during the course of PMN maturation [10].…”
Section: Introductionmentioning
confidence: 99%